Understanding Gender Neutral language at workplace: Study of TEVT schools of Nepal (Journal of Training and Development, 2016)
This study tries to understand how female instructors perceive use of gender neutral language in the workplace. Traditionally there had been stratification in male and female on the basis of work and also on the basis of language; but lately, a number of efforts have been made to remove stratification on the basis of gender. Still many reports argue that there is bias on the basis of gender language in the workplaces. The traditionally built stereotype on job roles of males and females given by the society people may not support and go in line with the practice of using gender neutral language. Therefore, this paper had aimed to explore the use of gender neutral language in technical schools of Nepal. To begin the study, eight female instructors from different technical schools of Nepal with different occupations were purposively selected. A case study research design was implied to understand the perception of female instruction with regards to gender neutral language in their work place.